Mind the trap:: Street art, visual literacy, and visual resistance - Bogerts, Lisa (Street Art & Urban Creativity, 2017)
Street art is used in political contexts by both powerful players and resistance movements. To understand how images make meaning and are constantly being negotiated between rule and resistance, a visual literacy must be fostered. I have therefore introduced an interdisciplinary methodology for critical visual analysis that allows for the differentiated examination of images in the interplay of rule and resistance and considers the specific features of street art. This analytical framework aims to foster a cross-fertilization between visual culture and political science and more specifically, International Relations.